(untitled) (Fiep Bulletin - online, 2011)
Health workers who work in hospitals are exposed to a multitude of risks that may directly affect their health and well being. The nurse is one of the employees likely to develop diseases in the work environment, and develop activities that expose them to different risks that may directly affect their health and well being. The objectives of this study was to characterize the socio-demographic profile of survey and assess the knowledge level of participants in the research on risks in your workplace, in light of the collective subject discourse. This is an exploratory study with quanti-qualitative approach, quantitative data were analyzed in Microsoft Excel, Windows XP version, using the index of frequency and percentage. Qualitative data were analyzed using the technique of the Collective Subject Discourse. The survey sample consisted of 60 professionals in the Nursing Team (28) 46% of the sample is aged 20 to 30 years (52) made up 87% for females, (34) 57% is in service between 0-5 years (42) 70% of survey participants are not updating courses (40) 67% of those surveyed suffered some type of accident at work, among these the most prevalent was the accident with bodily secretions (32) 36%, followed by sharp (25) 27%, perceived that the hospital workers’ knowledge about their health, specifically in addressing the occupational hazards, can be considered lightly. However, the solutions lead us to believe that, although health professionals promote care for the individual patient, know little about their own health care professional in relation to health - work - illness.